Analysis of The Utilization of Palm Oil Waste in Review From The Theory of Maslahah Case Study CV. Agro Hijau Aek Torop KM 5 Labuhan Batu - Putririani; Syakir, Ahmad; Syahbudi, Muhammad (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2024)
The area of smallholder oil palm plantations is directly proportional to the amount of waste produced, the Maslahah Theory plays a role here as a way to overcome it. However, with the waste of palm oil skewers on CV. Agro Hijau Aek Torop can make palm oil skewer waste that was once considered waste into a staple material with economic value. This study aims to find out how the impact of the use of oil palm sticks on increasing the income of the community's economic welfare in Aek Torop District. This study uses qualitative research methods. Data collection was carried out through in-depth interviews and then supported by literature studies. Results and research show that waste from palm oil produces finished goods of economic value such as bags, plates, serving hoods & baskets and thus can have a positive impact on the surrounding community by opening new jobs for the surrounding community so that it can increase community productivity and reduce the unemployment rate.